Intravascular stent composite coating material and preparation method thereof

By forming a polydopamine layer on the surface of the cardiovascular stent and combining chondroitin sulfate and bioactive peptide, the problems of poor hemocompatibility and delayed endothelialization of the existing cardiovascular stent surface are solved, and the excellent anticoagulation ability and rapid endothelialization of the stent are achieved.

CN119868668APending Publication Date: 2025-04-25ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110623.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing drug-eluting coating on the surface of the existing cardiovascular stent has poor blood compatibility and delayed endothelialization, which cannot effectively solve the problems of atherosclerotic plaques and coronary stenosis.

Method used

The polydopamine layer was formed by oscillating the dopamine solution, and then incubated in the mixed solution of bioactive peptides. Chondroitin sulfate was bound by electrostatic action, and the bioactive peptide reacted with Schiff base through Michael addition reaction to form a composite coating.

Benefits of technology

It significantly improves the anticoagulant ability of the vascular stent, selectively inhibits the proliferation of vascular smooth muscle, promotes rapid endothelialization of the stent, reduces the adhesion level of platelets and fibrinogen, and improves hemocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868668A_ABST
    Figure CN119868668A_ABST
Patent Text Reader

Abstract

The invention discloses an intravascular stent composite coating material and a preparation method thereof, and belongs to the technical field of material preparation. The chondroitin sulfate and bioactive peptide composite coating is constructed on the surface of the intravascular stent by adopting a surface modification technology, the blood compatibility of the composite coating material of the intravascular stent modified by the composite coating is greatly improved, and the chondroitin sulfate and bioactive peptide composite coating on the surface of the stent can remarkably promote proliferation of vascular endothelial cells; meanwhile, proliferation of vascular smooth muscle cells is inhibited, so that the vascular stent is endowed with excellent anticoagulation capability, vascular smooth muscle proliferation is selectively inhibited, and rapid endothelialization of the stent is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a vascular stent composite coating material and a preparation method thereof. Background Art

[0002] The main treatments for patients with cardiovascular diseases are drug therapy and surgical treatment. Drug therapy can only relieve the symptoms of cardiovascular diseases, stabilize plaques and prevent the occurrence of acute myocardial infarction, but it cannot fundamentally eliminate or shrink the existing atherosclerotic plaques or relieve coronary artery stenosis. Percutaneous coronary intervention with intravascular stents is widely used in the clinical treatment of patients with cardiovascular diseases because of its advantages such as less trauma, repeated stent placement in a short period of time, safety, effectiveness and patient benefits.

[0003] Most of the vascular stents currently in use are drug-eluting stents, which are made by directly coating a polymer coating loaded with anti-proliferative drugs on vascular stents such as stainless steel, nickel-titanium alloy, and cobalt-chromium alloy. The main disadvantages of existing cardiovascular stent coating technology are: (1) The cardiovascular stent coating is mainly composed of hydrophobic polymers, and the degradable polymer coating loaded with anti-cell proliferation drugs. Both the anti-cell proliferation drugs and the polymers are highly hydrophobic, which easily leads to plasma protein adsorption and platelet adhesion, poor blood compatibility, and easily causes coagulation on the stent surface. (2) The anti-cell proliferation drugs in the cardiovascular stent coating lack selectivity for vascular endothelial cells and smooth muscle cells. While inhibiting the proliferation of vascular smooth muscle, they also inhibit the growth and proliferation of vascular endothelial cells, resulting in a delay in the endothelialization process of the vascular stent, which is not conducive to vascular tissue repair and blood circulation reconstruction. Therefore, the development of a new coating material for cardiovascular stents is of great value in solving the problems existing in the existing drug-eluting stents used clinically. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a composite coating material for a vascular stent and a preparation method thereof, so as to solve the technical problems of poor blood compatibility and slow endothelialization of drug eluting coatings on the surface of existing cardiovascular stents.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: to provide a method for preparing a composite coating material for a vascular stent, comprising the following steps: placing the vascular stent material in a dopamine solution and oscillating it for 12-36 hours, so that dopamine undergoes a self-polymerization reaction on the surface of the vascular stent material, thereby forming a polydopamine layer on the surface of the vascular stent material; then washing, and then placing it in a bioactive peptide mixed solution for incubation for 4-8 hours, wherein the bioactive peptide mixed solution comprises chondroitin sulfate and bioactive peptides, wherein the chondroitin sulfate is bound to the surface of the vascular stent material through an electrostatic interaction with the polydopamine layer, and the bioactive peptides react with the dopamine layer through a Michael addition reaction and a Schiff base reaction, thereby grafting the bioactive peptides to the surface of the vascular stent material, and finally obtaining the composite coating material for the vascular stent.

[0006] On the basis of the above technical solution, the present invention can also be improved as follows:

[0007] Furthermore, the concentration of the dopamine solution is 0.5-2 mg / mL.

[0008] Furthermore, the oscillation temperature is 25-35°C and the rotation speed is 80-120 rpm.

[0009] Furthermore, the cleaning reagent is phosphate buffer.

[0010] Furthermore, the concentration of chondroitin sulfate is 1-5 mg / mL, and the concentration of the bioactive peptide is 1.5-2.5 mg / mL.

[0011] Furthermore, the concentration of chondroitin sulfate is 3 mg / mL, and the concentration of the bioactive peptide is 2 mg / mL.

[0012] Furthermore, the molecular weight of chondroitin sulfate is 50-200 kDa.

[0013] Furthermore, the amino acid sequence of the bioactive peptide is Cys-Ala-Gly, Cys-Gly-Cys-Ala-Gly or Cys-Gly-Gly-Cys-Ala-Gly.

[0014] Furthermore, the incubation temperature is 20-40°C.

[0015] The invention also discloses a vascular stent composite coating material prepared by the preparation method.

[0016] The beneficial effects of the present invention are:

[0017] 1. The composite coating material for vascular stent prepared by the present invention not only endows the vascular stent with excellent anticoagulant ability, but also selectively inhibits the proliferation of vascular smooth muscle and promotes the rapid endothelialization of the stent. The platelet adhesion level is significantly reduced, with a minimum reduction of 61%. At the same time, the fibrinogen adhesion level is also significantly reduced, with a minimum reduction of 81%, which indicates that the blood compatibility of the composite coating material for vascular stent is greatly improved after the composite coating is modified.

[0018] 2. After 1 day and 3 days of cell culture, the endothelial cell proliferation level of the vascular stent composite coating material samples increased by more than 3.2 times, while the proliferation of smooth muscle cells was significantly inhibited and the level did not increase significantly. This proves that the chondroitin sulfate and bioactive peptide composite coating on the stent surface can significantly promote the proliferation of vascular endothelial cells and inhibit the proliferation of vascular smooth muscle cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Comparison of platelet adhesion levels on sample surfaces;

[0020] Figure 2 Comparison of fibrinogen adhesion levels on sample surfaces;

[0021] Figure 3 Comparison of cell proliferation levels of endothelial cells after culture on the sample surface;

[0022] Figure 4 Comparison of cell proliferation levels of vascular smooth muscle cells after culture on the sample surface. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0024] Example 1

[0025] A method for preparing a composite coating material for a vascular stent comprises the following steps:

[0026] S1. Place the ZE21B magnesium alloy vascular stent in a 0.5 mg / mL dopamine solution (solvent is Tris-HCl solution, pH=8.5), oscillate in a constant temperature air bath oscillator at 25°C and 80 rpm for 36 hours, and then wash with phosphate buffer (pH=7.4);

[0027] S2. Take chondroitin sulfate with a molecular weight of 50 kDa and a bioactive peptide with an amino acid sequence of Cys-Ala-Gly and dissolve them in PBS solution to prepare a mixed solution with a chondroitin sulfate concentration of 1 mg / mL and a bioactive peptide concentration of 2 mg / mL; place the sample treated with S1 in the mixed solution and incubate at 20°C for 8 hours to obtain a vascular stent composite coating material.

[0028] Example 2

[0029] A method for preparing a composite coating material for a vascular stent comprises the following steps:

[0030] S1. Place the ZE21B magnesium alloy vascular stent in a dopamine solution with a concentration of 1 mg / mL (the solvent is Tris-HCl solution, pH=8.5), oscillate in a constant temperature air bath oscillator at 30°C and 100 rpm for 24 hours, and then wash with phosphate buffer (pH=7.4);

[0031] S2. Take chondroitin sulfate with a molecular weight of 100 kDa and a bioactive peptide with an amino acid sequence of Cys-Gly-Cys-Ala-Gly and dissolve them in PBS solution to prepare a mixed solution with a chondroitin sulfate concentration of 3 mg / mL and a bioactive peptide concentration of 2 mg / mL; place the sample treated with S1 in the mixed solution and incubate at 30°C for 6 hours to obtain a vascular stent composite coating material.

[0032] Example 3

[0033] A method for preparing a composite coating material for a vascular stent comprises the following steps:

[0034] S1. Place the ZE21B magnesium alloy vascular stent in a 2 mg / mL dopamine solution (solvent is Tris-HCl solution, pH=8.5), oscillate in a constant temperature air bath oscillator at 35°C and 120 rpm for 12 h, and then wash with phosphate buffer (pH=7.4);

[0035] S2. Take chondroitin sulfate with a molecular weight of 200 kDa and a bioactive peptide with an amino acid sequence of Cys-Gly-Gly-Cys-Ala-Gly, dissolve them in PBS solution to prepare a mixed solution with a chondroitin sulfate concentration of 5 mg / mL and a bioactive peptide concentration of 2 mg / mL; place the sample treated with S1 in the mixed solution, incubate at 40°C for 4 hours, and obtain a vascular stent composite coating material.

[0036] In the following experiments, A is a ZE21B magnesium alloy vascular stent sample; B is a vascular stent composite coating material sample prepared in Example 1; C is a vascular stent composite coating material sample prepared in Example 2; and D is a vascular stent composite coating material sample prepared in Example 3.

[0037] Experimental Example 1 Platelet Adhesion Experiment

[0038] For vascular stent coatings, it is usually necessary to have good anticoagulant function to avoid thrombosis after vascular stent implantation. The anticoagulant function of the chondroitin sulfate and bioactive peptide composite coating on the sample surface is evaluated through platelet adhesion experiments. The specific steps include:

[0039] Fresh blood was centrifuged at 1500 rpm for 15 min to obtain platelet-rich plasma. Four samples A, B, C, and D were placed in a 24-well cell culture plate. 50 μL of platelet-rich plasma was added to the surface of samples A, B, C, and D respectively, and incubated at 37°C for 60 min. The platelet adhesion enzyme-linked reaction kit (purchased from Beijing Solebow Technology Co., Ltd.) was then used to measure the absorbance of platelet adhesion on the sample surface. The results are as follows: Figure 1 shown.

[0040] In vitro platelet aggregation is generally considered to be a sign of thrombosis on the surface of materials. Studying the interaction between biomaterials and platelets is an important step in understanding their blood compatibility. As can be seen from the figure, the platelet adhesion level on the surface of sample A is the highest, and the platelet adhesion levels of samples B, C, and D are significantly reduced. This is mainly because chondroitin sulfate and bioactive peptides can inhibit platelet adhesion after modification, avoid platelet aggregation and activation, and thus improve the blood compatibility of vascular stent materials. Taking sample A as a reference, the platelet adhesion levels of samples B, C, and D are 0.72 times, 0.56 times, and 0.39 times that of sample A, respectively. As the content of chondroitin sulfate on the surface of the vascular stent material increases, the platelet adhesion levels of samples B, C, and D show a decreasing trend, all showing a lower platelet adhesion level, and the blood compatibility of the vascular stent material prepared by the present invention is improved.

[0041] Experimental Example 2 Fibrinogen Adhesion Experiment

[0042] Fibrinogen adhesion plays an important role in the coagulation process, so evaluating the effect of the surface coating of vascular stent samples on human fibrinogen adhesion can reflect the anticoagulant effect of the composite coating of chondroitin sulfate and bioactive peptides on the sample surface. The specific steps include:

[0043] (1) Take fresh blood and centrifuge it at 3500 rpm for 15 min to obtain platelet-poor plasma;

[0044] (2) 50 μL of platelet-poor plasma was added to samples A, B, C, and D respectively, incubated at 37°C for 60 min, and then removed and rinsed three times with saline;

[0045] (3) Add 200 μL of bovine serum albumin blocking solution to the surfaces of samples A, B, C, and D, block at 37°C for 30 min, and then rinse three times with saline;

[0046] (4) Add diluted horseradish peroxidase-labeled goat anti-human fibrinogen adhesion antibody (antibody: PBS = 1:500, v:v) to the surface of samples A, B, C, and D, incubate at 37°C for 60 min, rinse three times with saline and absorb the liquid;

[0047] (5) Add 100 μL of 3,3',5,5'-tetramethylbenzidine colorimetric solution, color for 10 min in dark, then add 50 μL of enzyme-linked immunosorbent assay termination solution, and then use a pipette to slowly draw 100 μL of liquid into a 96-well plate. Use an ELISA reader to measure the absorbance of each group of samples at 450 nm to evaluate the adhesion of each sample coating to fibrinogen in platelet-poor plasma. The results are shown in Figure 2. Figure 2 shown.

[0048] The surface of materials in contact with blood adsorbs nonspecific proteins, which can easily cause coagulation and thrombosis. Fibrinogen is a glycoprotein and the coagulation factor with the highest content in plasma; fibrinogen is an important reaction substrate for thrombosis and participates in the key steps of thrombosis. High fibrinogen is an important risk factor for various thrombotic diseases. Therefore, fibrinogen was selected as a model protein to evaluate the adsorption of nonspecific proteins on the surface of the material. As can be seen from the figure, the fibrinogen adhesion level on the surface of sample A is the highest. After modification with chondroitin sulfate and bioactive peptides, the fibrinogen adhesion level of the vascular stent material is significantly reduced. This is mainly because chondroitin sulfate and bioactive peptides greatly improve the blood compatibility of the surface of the vascular stent material. The fibrinogen adhesion levels of the three samples B, C, and D are 0.29 times, 0.35 times, and 0.19 times that of the fibrinogen adhesion level of sample A, respectively. This shows that after fibrinogen is modified on the surface of the chondroitin sulfate and bioactive peptide modified vascular stent material, the blood compatibility of the vascular stent material is significantly improved.

[0049] Experimental Example 3 Endothelial cell proliferation experiment

[0050] The CCK-8 method was used to evaluate the effect of the composite coating of chondroitin sulfate and bioactive peptides on the proliferation of endothelial cells. The specific steps include:

[0051] Endothelial cells were cultured at 8×10 3 Cells were inoculated at a density of 10 cells / mL in a 48-well cell culture plate and cultured in a constant temperature incubator at 37°C and 5% CO2. The cell culture medium was changed every day. After the cells were cultured for 1 day and 3 days, 80 μL of CCK-8 reagent was added to the cell culture medium, and the cells were cultured in the dark for 4 hours. Then 150 μL of the supernatant was extracted and the absorbance value was measured at 450 nm using an ELISA reader to evaluate the cell proliferation level of endothelial cells. The results are shown in Figure 3 shown.

[0052] Endothelial cells are cells located between blood and vascular tissue. They have a variety of complex physiological functions and play an important role in maintaining the normal function of the inner wall of blood vessels. As a coating applied to vascular stents, it is particularly important to explore its effect on vascular endothelial cells. At the same time, the functional endothelial layer also plays an important role in preventing thrombosis and restenosis in the stent. As can be seen from the figure, after vascular endothelial cells were cultured on the sample surface for 1 day and 3 days, the cell compatibility of sample A was poor, and there were fewer cells adhering to and growing on the sample surface. In addition to sample A, endothelial cells can grow and proliferate normally on the surfaces of samples B, C, and D, and the endothelial cell proliferation level after 3 days of culture is significantly higher than that after 1 day of culture. After 1 day and 3 days of culture, the cell proliferation levels of samples B, C, and D showed an overall increasing trend, which is related to the increase of chondroitin sulfate on the sample surface. Overall, after the three samples B, C, and D were modified with chondroitin sulfate and bioactive peptides, the cell compatibility with vascular endothelial cells was significantly improved, which is conducive to promoting the rapid endothelialization of vascular stent materials.

[0053] Experimental Example 4 Smooth muscle cell proliferation experiment

[0054] The CCK-8 method was used to evaluate the effect of the composite coating of chondroitin sulfate and bioactive peptides on the proliferation of smooth muscle cells. The specific steps include:

[0055] Vascular smooth muscle cells were cultured at 1×10 4The cells were inoculated at a density of 10 cells / mL in a 48-well cell culture plate and cultured in a constant temperature incubator at 37°C and 5% CO2. The cell culture medium was changed every day. After the cells were cultured for 1 day and 3 days, 80 μL of CCK-8 reagent was added to the cell culture medium, and the cells were cultured in the dark for 4 hours. Then 150 μL of the supernatant was extracted and the absorbance value was measured at 450 nm using an ELISA reader to evaluate the cell proliferation level of smooth muscle cells. The results are shown in Figure 4 shown.

[0056] Excessive proliferation of vascular smooth muscle cells after stent implantation is the main factor leading to intimal hyperplasia and in-stent restenosis. Inhibiting the abnormal proliferation of smooth muscle cells and accelerating endothelialization are important directions for the design of functional coatings for vascular stents. It can be seen from the figure that after 1 day and 3 days of smooth muscle cell culture, the endothelial cells on the surface of the four samples A, B, C, and D all showed different proliferation levels. Compared with sample A, the smooth muscle proliferation levels of the three samples B, C, and D were all reduced, which is closely related to the chondroitin sulfate and bioactive peptides modified on the surface of the vascular stent. Chondroitin sulfate and bioactive peptides have a certain inhibitory effect on the proliferation of vascular smooth muscle cells. In addition, the smooth muscle proliferation levels of the three samples B, C, and D showed a trend of gradual decrease, which is related to the increase in the content of chondroitin sulfate on the surface of the vascular stent material. After modification with chondroitin sulfate and bioactive peptides, the vascular stent material showed a certain inhibitory effect on the proliferation of vascular smooth muscle cells, which is beneficial to improve the ability of the vascular stent to inhibit intimal hyperplasia.

Claims

1. A method for preparing a composite coating material for a vascular stent, characterized in that: The following steps are involved: The vascular stent material is placed in a dopamine solution for oscillation for 12-36 hours, then washed, and then placed in a bioactive peptide mixed solution for incubation for 4-8 hours to obtain a vascular stent composite coating material; the bioactive peptide mixed solution includes chondroitin sulfate and bioactive peptides.

2. The method for preparing the composite coating material for a vascular stent according to claim 1, characterized in that: The concentration of the dopamine solution is 0.5-2 mg / mL.

3. The method for preparing the composite coating material for a vascular stent according to claim 1, characterized in that: The shaking temperature is 25-35°C and the rotation speed is 80-120 rpm.

4. The method for preparing the composite coating material for a vascular stent according to claim 1, characterized in that: The cleaning reagent is phosphate buffer.

5. The method for preparing the composite coating material for a vascular stent according to claim 1, characterized in that: The concentration of the chondroitin sulfate is 1-5 mg / mL, and the concentration of the bioactive peptide is 1.5-2.5 mg / mL.

6. The method for preparing the composite coating material for a vascular stent according to claim 5, characterized in that: The concentration of the chondroitin sulfate is 3 mg / mL, and the concentration of the bioactive peptide is 2 mg / mL.

7. The method for preparing the composite coating material for a vascular stent according to claim 5 or 6, characterized in that: The molecular weight of the chondroitin sulfate is 50-200 kDa.

8. The method for preparing the composite coating material for a vascular stent according to claim 5 or 6, characterized in that: The amino acid sequence of the bioactive peptide is Cys-Ala-Gly, Cys-Gly-Cys-Ala-Gly or Cys-Gly-Gly-Cys-Ala-Gly.

9. The method for preparing the composite coating material for a vascular stent according to claim 1, characterized in that: The incubation temperature is 20-40°C.

10. A composite coating material for a vascular stent, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.